Pengaruh Komitmen, Komunikasi, Semanga Kerja Dan Disiplin Kerja Terhadap Kinerja Organisasi - Uswatun Hasanah; Abdul Kodir Djaelani; Mohammad Rizal (UNIVERSITAS ISLAM MALANG, 2022)
AbstractThis study aims to determine the effect of Commitment, Communication, Morale and Work Discipline on the Performance of the Executive Board of Unisma Students for the 2020-2021 period. The type of research used is quantitative research with the method of distributing questionnaires. The sample in this study was 80 administrators and data processing using the SPSS computer program. This study has met the requirements of validity and reliability. The data analysis used in this study is the classical assumption test, multiple linear regression, hypothesis testing and coefficient of determination analysis. Against Performance. The results of this study conclude that the Commitment Variables, Communication, Work Spirit, have a partial effect on Performance, and Work Discipline had a partial effect on the Performance of the Student Executive Board of the Islamic University of Malang for the 2020-2021 Period. Keywords: Performance, Commitment, Communication, Morale And Work Discipline.